The fiscal program in recent Philippine history looking back and looking forward - Diokno, Benjamin E. (2017)
For almost four decades, the Philippines has underinvested in publici nfrastructure largely due to its severe macroeconomic challenges: low economic growth, high public debt, low revenues, and high interest rates. But the macroeconomic picture has significantly improved in recent years. Growth has accelerated amidst a low-inflation, low-interest rate environment. The debt-to-GDP ratio has gone down and continues to fall, while the revenue effort is projected to rise with the tax reform program. The favorable economic conditions have enabled the government to embark on an aggressive medium-term fiscal program that focuses on modernizing public infrastructure and investing in human capital development.

These developments are reflected in the 2017 national budget. Debt service as a share of the national budget has gradually declined from 20 percent in 1983-1985 and 30 percent in 1986-1996 to as low as 11 percent in 2017. By contrast, the share of social services has doubled from 21 percent in 1983-1985 to 40 percent in the 2017 while infrastructure and other capital outlays has more that quintupled from 1.1 percent in 1983- 1985 to 6.1 percent in 2017. The higher spending will be made possible by increasing the planned deficit from 2 percent to 3 percent of GDP combined with the higher revenue effort owing to the tax reform program.
Keywords: Fiscal policy; Infrastructure (Economics); Public debts